2022
DOI: 10.1093/jac/dkac361
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and immunovirological outcomes in patients with advanced HIV disease on their first antiretroviral treatment: differential impact of antiretroviral regimens

Abstract: Objectives To assess the clinical and immunovirological outcomes among naive patients with advanced HIV presentation starting an antiretroviral regimen in real-life settings. Methods This was a multicentre, prospective cohort study. We included all treatment-naive adults with advanced HIV disease (CD4+ T cell count < 200 cells/mm3or presence of an AIDS-defining illness) who started therapy between 2010 and 2020. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previous ndings [33][34][35] indicate older age may be a risk factor for incomplete CD4 + T cell recovery in PLWH, suggesting age may exert a strong effect on long-term recovery of CD4 + T cells. This was also found in the newly developed model, showing that median maximal CD4 + T cell count is higher in patients aged 16-32.5 years than in patients aged 32.5 years after ART treatment.…”
Section: Resultsmentioning
confidence: 93%
“…Previous ndings [33][34][35] indicate older age may be a risk factor for incomplete CD4 + T cell recovery in PLWH, suggesting age may exert a strong effect on long-term recovery of CD4 + T cells. This was also found in the newly developed model, showing that median maximal CD4 + T cell count is higher in patients aged 16-32.5 years than in patients aged 32.5 years after ART treatment.…”
Section: Resultsmentioning
confidence: 93%
“…Previous findings [ 32 , 36 , 37 ] indicate older age may be a risk factor for incomplete CD4 + T cell recovery in PLWH, suggesting age may exert a strong effect on long-term recovery of CD4 + T cells. This was also found in the newly developed model, showing that median maximal CD4 + T cell count is higher in patients aged 16–32.5 years than in patients aged 32.5 years after ART treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicentre European observational study, no difference in median CD4 cell count or CD4:CD8 ratio was observed 48 weeks after ART initiation with an INSTI or a PI among people with advanced HIV [4]. In the PISCIS cohort in Spain, people with advanced HIV were less likely to die and experienced faster virological suppression and CD4 cell count restoration when initiating ART with an INSTI than with a PI or non‐nucleoside reverse transcriptase inhibitors [5]. Similarly, among late‐presenting people with HIV (defined as CD4 <350 cells/μL or as either CD4 <350 cells/μL or ADE) in two Spanish cohorts, those initiating ART with an INSTI experienced favourable immunological outcomes compared with those initiating ART with other anchor agents [28, 32].…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, the prevalence of advanced HIV was estimated at 22% in 2015; the prevalence increases with older age (up to 37% among individuals aged ≥55 years) and by transmission category (34% among men with infection attributed to heterosexual contact; 29% among men with infection attributed to injection drug use) [3]. Individuals presenting with advanced HIV infection have an increased risk of HIV clinical progression, morbidity, and mortality [4][5][6][7][8][9]. In addition, advanced HIV is associated with an increased risk of HIV transmission, due to both higher viral loads and a longer period with unsuppressed viremia [6].…”
Section: Introductionmentioning
confidence: 99%